The Use of Noninvasive Mechanical Ventilation for the Treatment of Acute Exacerbations of Copd in Canada. Issue 3 (3rd April 2005) - Drummond, Jennifer; Rowe, Brian; Cheung, Lawrence; Mayers, Irvin
Abstract : BACKGROUND: Noninvasive mechanical ventilation (NIMV) is accepted as a life-saving treatment for patients presenting to the emergency department and other acute care settings with severe exacerbations of chronic obstructive pulmonary disease (COPD). OBJECTIVE: It was hypothesized that there is marked national variability in the use of NIMV. Therefore, the use of NIMV for COPD exacerbations in urban centres across Canada was evaluated. METHODS: All Canadian hospitals affiliated with a university training program were surveyed, and a request for involvement in this survey was posted on the Canadian Society of Respiratory Therapy professional practice listserv. Survey information was received from all 33 sites (100%) that were contacted. RESULTS: Marked differences in the application of NIMV were identified across all regions in Canada, ranging from requiring extensive monitoring in the intensive care unit to application on a general internal medical unit with intermittent noninvasive blood pressure monitoring. There were sites that rarely used NIMV for COPD exacerbations and others where it was routine practice. CONCLUSIONS: NIMV is a life-saving treatment for acute exacerbations of COPD. Despite clear clinical evidence, its use has not penetrated throughout all the larger urban hospitals in Canada. This may be more problematic in sites without 24 h respiratory therapy support. There are barriers to the routine application of NIMV that can be overcome using established guidelines and available evidence.